PROPELLER TURBINE DESIGN 625 WATT CAPACITY ON WATER TURBINE INSTALLATION FACULTY OF ENGINEERING UNSIKA - Firdaus, Daud (Dinamika : Jurnal Ilmiah Teknik Mesin, 2023)
The propeller turbine is a form of turbine as a means of converting flow energy into mechanical energy. The energy conversion involves several stages of energy change until finally it becomes mechanical energy. The installation that will be designed for a MHP in the Faculty of Engineering laboratory using a propeller turbine has a low water source and discharge. With a head of 2.56 m and a discharge of 0.0412 m3/S, it provides a shaft power of 625 Watts with an efficiency of 93.4%. To get high turbine efficiency, it is necessary to consider the installation of the built network and regulation of the flow direction through the turbine blades. The influence of the direction of flow hitting the blades will determine the size of the momentum generated.